2000
DOI: 10.1099/0022-1317-81-5-1217
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characterization of Kaposi’s sarcoma-associated herpesvirus/human herpesvirus-8 strains from Russia

Abstract: We report the molecular characterization, with subtyping of both K1 and K14.1/K15 genomic regions, of seven new human herpesvirus-8 (HHV-8) strains from Russian patients with classical Kaposi's sarcoma. Phylogenetic studies, based on the complete K1 gene/protein analysis, indicate that six of these strains belong to the A subtype, with one belonging to the A4 group and exhibiting a unique deletion of 19 amino acids in the VR2 region at position 186-204. PCR-based studies of the K14.1/K15 genomic region indicat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
28
0
3

Year Published

2002
2002
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(37 citation statements)
references
References 10 publications
6
28
0
3
Order By: Relevance
“…A comparison of PEL specimens and anatomically distinct KS lesions taken over time from nine individuals harbored identical viruses (551,552), suggesting that K1 variation does not occur over the lifetime of a single infected host. However, K1 genes isolated from biopsy specimens obtained 4 months apart in Russian patients had acquired up to 5 nucleotide and amino acid changes in four of the seven patients (276). Although these current PCR-based genotyping methods have suggested that infection by a single KSHV variant predominates, and may be exclusive, in many individuals, isolation of recombinant genomes argues strongly that coincident infection of a single host by different KSHV subtypes must occur.…”
Section: Kshv Subtypes and Geographic Variabilitymentioning
confidence: 98%
See 1 more Smart Citation
“…A comparison of PEL specimens and anatomically distinct KS lesions taken over time from nine individuals harbored identical viruses (551,552), suggesting that K1 variation does not occur over the lifetime of a single infected host. However, K1 genes isolated from biopsy specimens obtained 4 months apart in Russian patients had acquired up to 5 nucleotide and amino acid changes in four of the seven patients (276). Although these current PCR-based genotyping methods have suggested that infection by a single KSHV variant predominates, and may be exclusive, in many individuals, isolation of recombinant genomes argues strongly that coincident infection of a single host by different KSHV subtypes must occur.…”
Section: Kshv Subtypes and Geographic Variabilitymentioning
confidence: 98%
“…The M K15 allele was identified in 14 of 49 West and Central, but not East, African samples by Lacoste et al (275); however, it was not detected among 21 African KSHV specimens by Zong et al (with the exception of three U.S. AIDS patients with West African heritage) (551). In a small Russian cohort, four of seven samples harbored virus with M alleles (276). It has been postulated that the M K15 alleles are derived from a novel, possibly nonhuman, rhadinovirus by ancient recombination events and that the M allele may be evolving toward a higher prevalence in the population (551).…”
Section: Kshv Subtypes and Geographic Variabilitymentioning
confidence: 99%
“…In Europe and North America, groups A and C predominate (264). Geographic strain variation in gene sequences has been identified in viruses isolated from Japan, Kuwait, Europe, Russia, Australia, South America, and the United States (94,153,195,196,297). Although specific variants have not been associated with different pathologies, the high level of strain variability in HHV-8 may have important functional implications, although no serological differences have been noted using the currently available serological assays.…”
Section: Structure and Morphologymentioning
confidence: 99%
“…One hundred forty-five unique nucleotide sequences encoding all of ORF-K1 were collected from the National Center for Biotechnology Information (GenBank) (3,10,11,19). Sequences that contained in-frame insertions (including the putative K1-D strain sequences thus far reported) were excluded from the present analysis, and sequences that clustered weakly within K1-A, -B, and -C strains were also excluded.…”
mentioning
confidence: 99%